Population measures of subjective cognitive decline: A means of advancing public health policy to address cognitive health. Issue 1 (18th February 2021) - Olivari, Benjamin S.; Baumgart, Matthew; Taylor, Christopher A.; McGuire, Lisa C.
Abstract: Subjective cognitive decline (SCD) is receiving increasing attention as studies have suggested that SCD status is associated with risk of future cognitive decline and dementia. Population‐based measures of SCD can be extremely useful to the public health community, health‐care providers, researchers, and policymakers. A large population‐based SCD measure now exists through the state‐based Behavioral Risk Factor Surveillance System (BRFSS). All 50 states have included the cognitive decline module, which asks about SCD, to their BRFSS survey one or more times. Population measures of SCD can aid researchers in designing clinical studies by better estimating the populations that may be at risk for more severe cognitive decline based on their SCD status to ensure that the optimal groups are targeted. Population‐level estimates of SCD can also help to inform health‐care providers' decisions about initiating cognitive assessments, managing other conditions among those with memory problems, and identifying the needs of caregivers.